The Impact of Questioning Types on Students Critical Reading Skills - Munir, Munir; Arham, Muhammad; Saud, Chaerul Fadlan (Pascasarjana Universitas Negeri Makassar, 2025)
This study explores the effect of applying effective questioning types on university students’ critical reading skills. Many students in higher education face challenges when engaging with academic texts, often limiting their efforts to surface comprehension rather than deeper analysis. To address this issue, the study implemented a framework of questioning—analytical, evaluative, interpretive, inferential, and synthetic—designed to promote higher-order thinking. A pre-experimental design was employed using a one-group pre-test and post-test format with 45 undergraduate students from English Education Study Program, Faculty of Languages and Literature Universitas Negeri Makassar, Indonesia. Over four sessions, students were guided through structured questioning activities aimed at encouraging deeper engagement with reading materials. Data were collected using essay-based critical reading tests, and scores were verified by two independent raters to ensure reliability. Findings indicated a significant improvement in students’ performance, with mean scores rising from 61.8 on the pre-test to 72.4 on the post-test. The Wilcoxon Signed-Rank Test (Z = -5.037, p < .001) confirmed that this improvement was statistically significant. The results suggest that structured questioning fosters analytical, interpretive, and evaluative engagement with texts, thereby bridging the gap between comprehension and critical literacy. The study contributes to reading pedagogy by demonstrating the role of questioning in cultivating reflective and independent readers at the university level. It recommends that lecturers integrate varied questioning strategies into reading instruction to strengthen students’ academic literacy and prepare them for the demands of higher education.